Heavy Alcohol Use Among Deceased Donors Does Not Impact Recipient Outcomes After Liver Transplantation. Issue 11 (November 2018) - Arora, Sumant S.; Chahal, Khushdeep S.; Axley, Page; Eckhoff, Devin E.; Kuo, Yong-Fang; Satapathy, Sanjaya K.; Wiesner, Russell; Singal, Ashwani K.
Abstract : Background: Data on liver transplant (LT) outcomes using deceased donors with heavy drinking (HD) (>2 drinks per day) are scanty. Methods: Using the United Network for Organ Sharing database (2002-2014), we examined outcomes after LT in adults comparing deceased HD donors with non-HD (ND) donors. Results: Of 56 182 first LTs performed in the United States for 10 common indications using deceased donors, 47 882 with available information on alcohol use were analyzed. Of these 47 882 LT recipients, 7298 (15%) were from HD donors, with similar proportion over time (2002-2014, Armitage trend test P = 0.75) and for recipient liver disease etiology (χ 2 P = 0.42). Proportion of liver organ used for LT was lower for HD donors compared with ND donors (63% vs 78%; P < 0.001). Five-year outcomes on first LT comparing 7166 HD donors and 21 498 ND donors matched based on propensity score were similar for liver graft (73.7% vs 73.7%, log rank P = 0.98) and patient survival (77.6% vs 77.0%, P = 0.36). On Cox regression analysis, history of HD in deceased donors did not affect liver graft 1.02 (0.97-1.08) or patient survival 1.03 (0.97-1.09). Conclusions: Among LT recipients using select liver grafts, history of HD in deceased donors does not impact outcomes after LT. Abstract : Using the United Network for Organ Sharing database (2002-2014), the authors examine postliver transplantation outcomes in adults comparing deceased donors with heavy drinking (HD) with not heavy drinking donors and conclude that history of HD in deceased donors does not appear to impact graft or patient survival. Supplemental digital content is available in the text.